ANALISIS PEMAHAMAN SISWA KELAS V SD NEGERI 136 PEKANBARU DALAM PENGGUNAAN HURUF KAPITAL - Pratiwi, Lunik; Kurniaman, Otang; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is based by the problem of grade 5 students in writing.In writing letters students often make a mistake. Some mistake was in writing letterswhich is the procedure of writing capital letters. Students often make a mistake in thebeginning of a sentence, people’s name, important places, job title, and essay’s title.This is the problem that often found in teaching writing at school. This research aims todescribe and analyze the understanding of grade 5 students of SD Negeri 136Pekanbaru in using capital letters. The research method is using descriptivequantitative research methods with subjects all of grade 5 SD Negeri 136 Pekanbaruwith the number of 120 students. The data collection techniques are using test, with aresearch instrument that is the understanding of using capital letters as many as 36questions. Based on the research results, there are 12 students that were in an excellentcategory 10%, 20 students in a good category 16.67%, 40 students in sufficientcategory 33.33%, and 48 students in worse category 40%. Overall, students gainunderstanding of 55.69% with sufficient category. This illustrate that understanding thegrade 5 students of SD Negeri 136 Pekanbaru in understanding capital letters issufficient.Key Words: Understanding, capital letters